O Campeonato do Mundo de Futebol de 2010 na África do Sul: Uma análise política e económica - Rodrigo Quintas da Silva (Cadernos de Estudos Africanos)
In the current globalized era, organizing a sports mega-event represents for the hosting country a great opportunity of acquiring visibility, notoriety and promotion overseas. To emerging countries, this is of even greater relevance for it facilitates their integration together with their more powerful counterparts. For South Africa, accommodating the 2010 FIFA World Cup enabled it to innovate in this area by employing sports as an apparatus to reinforce and project its power to the outside world. Such a concept would eventually establish its profile through the attraction of capital investments and increasing tourism flows as a consequence of the mega-event. Nevertheless, the benefits of this instrument of power are not as clear as it was estimated. In fact, some relevant indicators have witnessed a decrease in growth rate in the period after the 2010 FIFA World Cup.